A Molecular Mechanism-Based Approach: Differences in the Roles of Berberine, Quercetin and Baicalin in the Treatment of Breast Cancer - Zhou, Yingru (International Journal of Public Health and Medical Research, 2025)
Breast cancer is considered one of the most prevalent types of malignant tumours among women worldwide, and recent academic studies have revealed that natural products highlight a key role in the intervention and treatment of breast cancer. The present study focused on three typical natural active compounds, berberine, quercetin and baicalin. It investigates their molecular pathways and functional heterogeneity in the field of breast cancer therapy, further compares the characteristics of the molecular mechanisms of each of the three compounds and their differences in the treatment of breast cancer, and at the same time deeply discusses their potential application value in combination therapy strategies as well as their future development trends in the field of breast cancer therapy.